2006
DOI: 10.1111/j.1365-2036.2006.03036.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: are antibiotics detrimental or beneficial for the treatment of patients with Escherichia coli O157:H7 infection?

Abstract: SUMMARY BackgroundEscherichia coli O157:H7 is a foodborne pathogen causing haemorrhagic colitis, which is sometimes complicated by haemolytic uraemic syndrome or thrombotic thrombocytopenic purpura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 67 publications
0
59
0
4
Order By: Relevance
“…Currently, there is no vaccine available to humans to prevent infection by EPEC or EHEC, and the use of antibiotics for treatment of EHEC infections is controversial as certain antibiotics may exacerbate disease symptoms (Panos et al 2006), as well as induce Shiga toxin production. Numerous EHEC outbreaks have been traced back to ingestion of contaminated beef and vegetable products (Nataro and Kaper 1998;Berger et al 2010).…”
Section: Epec Infection Modelsmentioning
confidence: 99%
“…Currently, there is no vaccine available to humans to prevent infection by EPEC or EHEC, and the use of antibiotics for treatment of EHEC infections is controversial as certain antibiotics may exacerbate disease symptoms (Panos et al 2006), as well as induce Shiga toxin production. Numerous EHEC outbreaks have been traced back to ingestion of contaminated beef and vegetable products (Nataro and Kaper 1998;Berger et al 2010).…”
Section: Epec Infection Modelsmentioning
confidence: 99%
“…A number of metaanalyses and systematic reviews have attempted to summarize the results of available studies, reaching inconclusive results and stating that more prospective, appropriately powered studies are needed. [55][56][57] Most studies found no difference or favored a negative impact of antibiotics on risk for D+HUS and outcome. 55,56 Only one retrospective cohort analysis of a large outbreak that occurred in Japan, demonstrated benefit for using the antibiotic fosfomycin within the first 2-3 days from beginning of EHEC infection symptoms.…”
mentioning
confidence: 99%
“…[55][56][57] Most studies found no difference or favored a negative impact of antibiotics on risk for D+HUS and outcome. 55,56 Only one retrospective cohort analysis of a large outbreak that occurred in Japan, demonstrated benefit for using the antibiotic fosfomycin within the first 2-3 days from beginning of EHEC infection symptoms. 50,58 The negative impact of antibiotic use on risk and outcomes of HUS is not well understood.…”
mentioning
confidence: 99%
“…Two systematic reviews [4,5] assessing HUS risk after antibiotic antibiotic administration to STEC-infected patients concluded that they neither decreased nor increased the likelihood of this complication. The first meta-analysis reported a pooled odds ratio (OR) of 1.15 (95% confidence interval [CI], .79-1.68), but had methodological limitations.…”
mentioning
confidence: 99%